1985
DOI: 10.1080/00913847.1985.11708746
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Excellence: It's a Matter of Mind and Body

Abstract: In brief: Human thought is a complex, sophisticated, amazing, and ongoing process. It cannot be ignored when considering success in sports competition. Until recently, however, mental training has not received as much attention as physical training. This article discusses how athletes may achieve optimal emotional arousal levels in accordance with their specific sports and individual personalities. Self-talk, muscle relaxation, and deep breathing are among the techniques they can use. With practice, athletes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Landin proposed that self-talk can be used to enhance attentional focus, whereas Nideffer indicated that self-talk can be an effective strategy for directing attention to task relevant cues. Finn (1985) and Zinnser et al (2006) suggested that self-talk can regulate effort and enhance self-confidence, whereas Hardy et al (1996) argued that self-talk can also be effective in controlling anxiety. Hatzigeorgiadis (2006) in his research, was examined the perceived functions of instructional and motivational self-talk.…”
Section: Jpes ®mentioning
confidence: 99%
“…Landin proposed that self-talk can be used to enhance attentional focus, whereas Nideffer indicated that self-talk can be an effective strategy for directing attention to task relevant cues. Finn (1985) and Zinnser et al (2006) suggested that self-talk can regulate effort and enhance self-confidence, whereas Hardy et al (1996) argued that self-talk can also be effective in controlling anxiety. Hatzigeorgiadis (2006) in his research, was examined the perceived functions of instructional and motivational self-talk.…”
Section: Jpes ®mentioning
confidence: 99%
“…Landin (1994) supported an attentional interpretation of ST effects, indicating that ST can be used to enhance attentional focus and direct or redirect attention to task-relevant cues. Finn (1985) and Zinsser et al (2001) suggested that ST serves to regulate effort and enhance confidence, whereas Hardy, Jones, and Gould (1996) speculated that ST can also be effective in controlling anxiety and triggering appropriate action.…”
mentioning
confidence: 96%
“…On the one hand, Finn (1985) and Zinsser, et al (2006) argued that self-talk could promote greater confidence and regulation of effort, while Hardy, Jones, and Gould (1996) suggested that self-talk may aid in coping with anxiety and prompting suitable actions. On the other hand, Landin (1994) and Nideffer (1993) proposed that the effects of self-talk on performance could be explained by its effect on the athletes' attention.…”
mentioning
confidence: 99%
“…With increasing evidence in favour of the eff ectiveness of self-talk re-increasing evidence in favour of the effectiveness of self-talk regarding performance enhancement, the focus of research has shifted toward the identification of the specific mechanisms through which self-talk aids performance (Hardy, 2006). On the one hand, Finn (1985) and Zinsser, et al (2006) argued that self-talk could promote greater confidence and regulation of effort, while Hardy, Jones, and Gould (1996) suggested that self-talk may aid in coping with anxiety and prompting suitable actions. On the other hand, Landin (1994) and Nideffer (1993) proposed that the effects of self-talk on performance could be explained by its effect on the athletes' attention.…”
mentioning
confidence: 99%